If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -1 * 1 Multiply -1 * 1 y = -1 Solving y = -1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -1
| 7/12x9/2-33/40 | | 4/5b=120 | | 4/5b=48 | | y=-3/4*1+6 | | -0.75*-3/4x+6 | | x^2+5x-37.5=0 | | 96x^2-204x-99=0 | | 450+0.06s=0.06s+900 | | x-43=0 | | 3(6s+12)-10s-6=0 | | 6*4-4y=-24 | | 15c^2-17c-42=0 | | 6x-4*4=-24 | | x^2-x-169=0 | | 13x+10y=20 | | 44x+7=x | | 3(n)+7=46 | | (1/2)x-15=30 | | 2(x+5)-8= | | =165(2.1)0.09t | | 26x+5y=31 | | 3w^2-11w-4=0 | | 14x+14=6x-32 | | 5=0.04x+0.8 | | 3b^2+2b-5=0 | | 5x=90-9y | | 5x=90-9x | | (3)/(4+2i) | | 14x+16=6x-32 | | -2=8*0-2 | | -2x-3=3x-13 | | 2x+14=96 |